ORGANIZATION AND CONDUCT OF MILITARY-PATRIOTIC EDUCATION AT THE FACULTIES OF MILITARYEDUCATION (Web of Discoveries: Journal of Analysis and Inventions, 2023)
The purpose, direction and content of the education of military patriotism in a general education school. Principles, forms and methods of education of military patriotism. Duties of the director of the educational institution, military commander and cadets on the organization and conduct of military-patriotic education. The initial committee of the organization of defense "Patriot" and the role of the family in the education of military patriotism. Organization of education of military patriotism at training camps in military sports health camps. Studies have been conducted on the organization of military fatherhood